2005
DOI: 10.1016/s1808-8694(15)31241-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in septoplasty: is it necessary?

Abstract: The nasal surgeries are clean contamined and do not need antibioticprophilaxy because of the low infection risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 10 publications
0
45
0
1
Order By: Relevance
“…Based on the best available evidence, current guidelines and review articles recommend the use of antimicrobial prophylaxis for the majority of cleancontaminated procedures. [6][7][8]497,520,521 However, antimicrobial prophylaxis did not lower infection risk in randomized controlled trials of patients undergoing adenoidectomy, tonsillectomy, 522,523 and septoplasty, 524 and systematic reviews have not recommended prophylaxis for these procedures. 7,525,526 The efficacy of antimicrobial prophylaxis is best established for head and neck cancer surgery.…”
Section: Head and Neck Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the best available evidence, current guidelines and review articles recommend the use of antimicrobial prophylaxis for the majority of cleancontaminated procedures. [6][7][8]497,520,521 However, antimicrobial prophylaxis did not lower infection risk in randomized controlled trials of patients undergoing adenoidectomy, tonsillectomy, 522,523 and septoplasty, 524 and systematic reviews have not recommended prophylaxis for these procedures. 7,525,526 The efficacy of antimicrobial prophylaxis is best established for head and neck cancer surgery.…”
Section: Head and Neck Proceduresmentioning
confidence: 99%
“…Studies of cleancontaminated head and neck procedures found no difference in efficacy between regimens of 24 hours and longer regimens of three, five, or seven days. [499][500][501]505,507,512,524,[531][532][533][534] Limited data exist on single-dose prophylaxis in these procedures.…”
Section: Head and Neck Proceduresmentioning
confidence: 99%
“…In the otolaryngologic field, transient bacteremia has been reported in many operation types, including septorhinoplasty, endoscopic sinus surgery, tonsillectomy, adenoidectomy, mastoidectomy, and tympanoplasty [26][27][28][29]. In the literature, only one study has demonstrated the relationship between bacteremia and the amount of bleeding; a significant correlation was observed during adenotonsillectomy [30].…”
Section: Discussionmentioning
confidence: 99%
“…8 Indiscriminate use of antibiotics can also cause toxic reactions. 9 Hence, judicious use of antibiotics is necessary.…”
Section: Aureusmentioning
confidence: 99%